Synonymies of anomalous species of Arrhopalites from Australia and New Zealand - Greenslade, Penelope (Zootaxa, 2011)
Characters of two species, described more than seventy years ago in the genus Arrhopalites Börner, A. coccineus Salmon, 1941 and A. adelaidica Womersley, 1933, are not consistent with the current diagnosis of the genus. Instead, the holotype of A. coccineus and two cotypes of A. adelaidica, but not the lectotype, are consistent with characters of Stenacidia violacea (Reuter, 1881) following the description of the genus and species published by Bretfeld (1999). Stenacidia violacea is the type species of its monotypic genus. As the characters of the genus Stenacidia, following Bretfeld (1999), are very different to those of Arrhopalites, but are consistent with the characters of A. coccineus and two cotypes of A. adelaidica, A. coccineus is synonymised with S. violacea here and identification of the cotypes of A. adelaidica corrected.